SUPERVISI AKADEMIK KEPALA SEKOLAH DAN DISIPLIN KERJA GURU TERHADAP PRODUKTIVITAS KERJA GURU SD NEGERI SE KECAMATAN MUMBULSARI JEMBER - Sulistyaningsih Sulistyaningsih (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
This study aims to determine the influence/contribution of school headmasters' academic supervision and teacher work discipline on the work productivity of state elementary school teachers in Mumbulsari District, Jember Regency. This is a quantitative survey research with the number of sample is 148 peoples. Data collection tool is questionnaire with regression techniques for data analysis. The results of this study show that: (1) There is a positive and significant influence between the school headmasters’ academic supervision on the teachers’ work productivity in state elementary schools in Mumbulsari District, Jember Regency. (2) There is a positive and significant influence between teachers’ work discipline on teachers’ work productivity of state elementary schools in Mumbulsari District, Jember Regency. (3) There is a positive and significant influence simultaneously on the school headmasters' academic supervision and teacher work discipline on the work productivity of public elementary school teachers in Mumbulsari District, Jember Regency at 59.1%, while as many as 40.9% are influenced by factors other than the headmasters' academic supervision and teacher work discipline. Thus, both of these variables can be used as predictors of the trend of increasing work productivity of public elementary school teachers in Mumbulsari District, Jember Regency.